Suplemen Pembelajaran Akidah Akhlak Materi Sifat Wajib 20 di MTs Kelas 7 - Farhanul; Ulil Amri Syafri; Abdul Hayyie Al-Kattani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research is motivated by the phenomenon of moral degradation among adolescents in the digital era, which has become increasingly complex and therefore requires the strengthening of theological foundations through Islamic educational institutions. Aqidah Akhlak serves as a fundamental pillar in the formation of religious character. However, field observations indicate that the material on the Twenty Essential Attributes (Sifat Wajib 20) of Allah lacks adequate instructional resources and relies excessively on textual memorization. This condition causes seventh-grade students of Madrasah Tsanawiyah (Islamic junior high school) to experience difficulties in internalizing abstract theological concepts into logical, profound, and practical understandings applicable to their daily lives. The primary objective of this study is to design, develop, and evaluate the feasibility of an innovative and adaptive Aqidah Akhlak learning supplement for Madrasah Tsanawiyah students. The research employs a Research and Development (R&D) method using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The focus of product development lies in integrating rational arguments (dalil ‘aqli) and scriptural arguments (dalil naqli) to stimulate critical thinking while simultaneously strengthening students’ faith through more communicative and contextualized learning materials. Based on the validation results, the product achieved an average score of 82.02% from subject-matter experts, categorized as “Feasible.” Meanwhile, the evaluation from educational practitioners (subject teachers) yielded a score of 93.27%, categorized as “Highly Feasible.” These findings demonstrate that the supplement not only meets rigorous academic standards but also possesses strong practical relevance to the cognitive characteristics of junior secondary students. In conclusion, the implementation of this supplement is effective as a complementary instructional medium capable of enhancing substantive theological under.